Indoor air pollution, physical and comfort parameters related to schoolchildren's health: Data from the European SINPHONIE study - Baloch, Ramen Munir; Maesano, Cara Nichole; Christoffersen, Jens; Banerjee, Soutrik; Gabriel, Marta; Csobod, Éva; de Oliveira Fernandes, Eduardo; Annesi-Maesano, Isabella; SINPHONIE Study group (The Science of the total environment, 2020)
Substantial knowledge is available on the association of the indoor school environment and its effect among schoolchildren. In the same context, the SINPHONIE (School indoor pollution and health: Observatory network in Europe) conducted a study to collect data and determine the distribution of several indoor air pollutants (IAPs), physical and thermal parameters and their association with eye, skin, upper-, lower respiratory and systemic disorder symptoms during the previous three months. Finally, data from 115 schools in 54 European cities from 23 countries were collected and included 5175 schoolchildren using a harmonized and standardized protocol. The association between exposures and the health outcomes were examined using logistic regression models on the environmental stressors assessed in classroom while adjusting for several confounding factors; a VOC (volatile organic compound) score defined as the sum of the number of pollutants to which the children were highly exposed (concentration > median of the distribution) in classroom was also introduced to evaluate the multiexposure - outcome association. Schoolchildren while adjusting for several confounding factors. Schoolchildren exposed to above or equal median concentration of PM2.5, benzene, limonene, ozone and radon were at significantly higher odds of suffering from upper, lower airways, eye and systemic disorders. Increased odds were also observed for any symptom (sick school syndrome) among schoolchildren exposed to concentrations of limonene and ozone above median values. Furthermore, the risks for upper and lower airways and systemic disorders significantly increased with the VOCs score. Results also showed that increased ventilation rate was significantly associated with decreased odds of suffering from eye and skin disorders whereas similar association was observed between temperature and upper airways symptoms. The present study provides evidence that exposure to IAPs in schools is associated with various health problems in children. Further investigations are needed to confirm our findings.
Keywords: Indoor air pollution; Temperature; Thermal parameters; VOC; Child; Europe; dítě; Air Pollution; Sick building syndrome; Allergy; látky znečišťující vzduch; Evropa; Schools; znečištění ovzduší; školy; lidé; Humans; Multi-pollution; teplota; znečištění vzduchu ve vnitřním prostředí; Air Pollution, Indoor; Air Pollutants